(untitled) (Advancements in Homeopathic Research, 2024)
Background: Existing scales for Alopecia measures severity and stages, all of which are made for individual types, none of the existed ones can be applied to all types and no one focuses on the clinical symptoms which patient addresses while case taking or can be used to assess the clinical outcomes. So, a scale was developed on the basis of existing literatures which can assess the clinical outcomes and can be apply for all types of alopecia. Objective: To develop alopecia scoring scale to clinically assess overall hair and scalp condition based on compilation of existing literature and to test the reliability and validity of alopecia scoring scale. Material & Methodology: Alopecia scoring scale was derived after thorough literature review. A pilot study was conducted on 30 patients who are clinically diagnosed with alopecia in July 2021 at Swasthya Kalyan Homoeopathic Medical College & Research Centre, Sitapura, Jaipur. Result: The internal consistency of scale were estimated by Cronbach Alpha Coefficient which was found to be generally satisfactory. The Cronbach Alpha reliability coefficient 0.82 which suggests it was found to be reliable. Pearson’s Co-relation Coefficient obtained value is > 0.7 which is greater than critical value of 0.361 at df 28 and is highly significant, so it is a valid scale. Conclusion: The Alopecia Scoring Scale is the valid and reliable tool to clinically access all types of Alopecia patients. It might serve as a useful tool to monitor disease status over time, and to guide treatment decisions.